THE STUDY OF POLITICAL PROCESSES IN CENTRAL ASIA AND THE RUSSIAN EMPIRE'S INVASION IN THE LATE 19TH CENTURY IN ARAB HISTORIOGRAPHY (Scientific journal of the Fergana State University, 2024)
This article examines the history of Central Asia in the Arab states in the 19th century, including the geopolitical situation in the region, the relationship between the khanates, the invasion of the Russian Empire and the study of its consequences. Arab historiography also covers ideas about the Turkestan region, its geographical space, population, political and historical processes. The reasons for studying the history of Central Asia in Arab countries, including Uzbekistan, the sources of Arab scientists, and their connection with political events are analyzed. The rulers of the Khanate in Central Asia and their personalities were also studied by Arab scholars and described in works in chronological order. Unique methods and conclusions of covering the historical process in Arab countries are explored.